EFEKTIVITAS CAMPURAN EKSTRAK BABANDOTAN DAN KIRINYUH SEBAGAI BIOHERBISIDA GULMA SEMBUNG RAMBAT (Mikania micrantha) - Sarwendah; Sopiana (Politeknik Negeri Ketapang, 2026)
Sembung rambat typically grows dominantly in immature oil palm plantations, often to the point of twining around or smothering the cultivated crops. Bioherbicides are increasingly being developed as alternatives to chemical herbicides, which are known to have negative environmental impacts. Blending bioherbicide extracts results in a higher concentration of allelochemical compounds, thereby enhancing weed control effectiveness. Kirinyuh and babandotan are plants with potential for use in such extract blends. This study aimed to determine whether a mixture of babandotan and kirinyuh extracts could kill sembung rambat weeds. A Completely Randomized Design (CRD) was employed, comprising five treatments (0%, 12.5%, 25%, 37.5%, and 50%) with four replications, resulting in 20 experimental units; each unit contained four samples, making a total of 80 sembung rambat weed samples. Observed parameters included time to death, mortality percentage, fresh weight, dry weight, and qualitative bioherbicide analysis. Data were analyzed using Analysis of Variance (ANOVA). If significant effects were found, Duncan’s Multiple Range Test (DMRT) was conducted at the 5% significance level. The analysis of variance results indicated that the application of the babandotan and kirinyuh extract mixture had a significant effect on the time to death, mortality percentage, fresh weight, and dry weight of sembung rambat weeds. Based on the DMRT results, the 50% concentration of the babandotan and kirinyuh extract mixture was the most effective at increasing sembung rambat weed mortality.